Implant Materials: Assessment of Novel Long‐Lasting Ceria‐Stabilized Zirconia‐Based Ceramics with Different Surface Topographies as Implant Materials (Adv. Funct. Mater. 40/2017). (24th October 2017) - Altmann, Brigitte; Karygianni, Lamprini; Al‐Ahmad, Ali; Butz, Frank; Bächle, Maria; Adolfsson, Erik; Fürderer, Tobias; Courtois, Nicolas; Palmero, Paola; Follo, Marie; Chevalier, Jérôme; Steinberg, Thorsten; et al.
Abstract : The histological image on the cover displays the interface between a ceramic implant and newly formed bone tissue (red). In article number1702512, Brigitte Altmann and co‐workers reveal in a preclinical evaluation screening using human cells, an animal model, and in situ microbiological methods, a new ceria‐stabilized zirconia‐alumina‐aluminate composite ceramic in conjunction with a porous surface topography as superior implant material for clinical applications.